2018
DOI: 10.1177/0272989x18759933
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Cognitive and Affective Mechanisms that Underlie Proxy Risk Perceptions among Caregivers of Asthmatic Children

Abstract: Heuristic judgment processes appear to contribute to caregivers' proxy risk perceptions of their child's asthma exacerbation risk. Moreover, the display of other, possibly erroneous, judgment phenomena is associated with lower caregiver risk perceptions. Designing interventions that target these mechanisms may help caregivers work with their children to reduce exacerbation risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…[27][28][29] At the same time, the use of heuristics in parents' decision making may lead to unrealistic optimism related to future risks. 30 Future research should compare reactions to a future risk of obesity with other future health risks. In some settings, such as decisions about high-risk treatments for chronic illness, parents do consider long-term risks, 31 indicating that there are at least some situations in which parents integrate both short-and long-term risks into their decision process.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] At the same time, the use of heuristics in parents' decision making may lead to unrealistic optimism related to future risks. 30 Future research should compare reactions to a future risk of obesity with other future health risks. In some settings, such as decisions about high-risk treatments for chronic illness, parents do consider long-term risks, 31 indicating that there are at least some situations in which parents integrate both short-and long-term risks into their decision process.…”
Section: Discussionmentioning
confidence: 99%
“…More evidence comes from a study concerning adult caregivers of children with asthma. Most of them believed that their child’s asthma was better controlled than other children with this disease (Shepperd et al, 2018). Thus, it is also clear that during the COVID-19 threat, BTAE may serve an important role not only in understanding people in the present crisis per se but also – more importantly – in projecting future interventions to make societies more eager to follow medical recommendations, which in turn would help to fight future global health crises.…”
Section: Comparing With Others In a Moment Of Crisis: Better-than-ave...mentioning
confidence: 99%
“…On the grounds of health psychology—which is especially important for the scope of this article—it was demonstrated that participants rated their eating behaviors as healthier ( Sproesser et al, 2015 ) and perceived themselves as more “energetic” ( Bowen et al, 2020 ). It was also reported that adult caregivers of children with asthma believed that their child’s asthma was better controlled by them ( Shepperd et al, 2018 ).…”
Section: Biased Social Comparisonsmentioning
confidence: 99%